Evaluation of the recurrence and fertility rate following salpingostomy in patients with tubal ectopic pregnancy - Tahereh Poordast; Zahra Naghmehsanj; Razie Vahdani; Shaghayegh Moradi Alamdarloo; Mohammad Ali Ashraf; Almtaj Samsami; Fatemeh Sadat Najib (BMC, 2022)
Abstract Background Ectopic pregnancy is one of the leading causes of pregnancy-related mortality; the treatment strategies associated with this condition entail complications, such as recurrence of ectopic pregnancy or infertility. The objective of this study was to evaluate the recurrence and fertility rate after salpingostomy in patients with tubal ectopic pregnancy. Methods This cross-sectional retrospective study was conducted at four referral centers of Obstetrics and Gynecology, under the supervision of Shiraz University of Medical Sciences (Iran). The medical records of 125 patients with tubal pregnancy were reviewed. These patients underwent laparoscopic salpingostomy from April 2009 to March 2016.Data on maternal age, BMI, history of previous EP, genital tract infection, IUD insertion, history of previous surgery, and infertility were further obtained. The patients were followed up for approximately 1 to 7 years. The recurrence of EP and subsequent pregnancy rate were assessed during the follow-up period. Results There was no statistically significant relationship between post-salpingostomy recurrence and maternal age, previous abdominopelvic surgery, and history of infertility(P = .425); however, the post-salpingostomy recurrence of EP was correlated with BMI (P = 0.001), previous history of EP (P = 0.001), genital tract infection (P = 0.001), and IUD insertion (P = 003). Among 95 women who had no contraception, pregnancy occurred in 51 cases (53.6%) and recurrence of EP was observed in 16 patients (12.8%). Conclusions Our results suggest that salpingostomy is a safe method with a low risk of recurrence and good fertility outcomes for women who consider future pregnancy.